2019
DOI: 10.1097/mao.0000000000002397
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Not Associated With Postoperative Complications After Vestibular Schwannoma Surgery in a Large Single Institution Series

Abstract: Objective: Determine whether elevated body mass index (BMI) is associated with postoperative complications after vestibular schwannoma (VS) surgery. Study Design: Retrospective case series. Setting: Tertiary referral center. Patients: Two hundred six patients undergoing surgery for VS between 2010 and 2017, grouped into obese and nonobese patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 24 publications
3
19
1
Order By: Relevance
“…[11][12][13] A recent institutional study by Lipschitz and colleagues demonstrated that obesity was not a risk factor for most post-operative complications. 22 Similar to that study, we found increased BMI to be associated with post-operative cardiovascular complications, which is in-line with previous studies acknowledging obesity as a risk factor for MI. 23 Though our observed association between obesity and wound infections or severe obesity and DVT are not in-line with Lipschitz et al, 22 these finding resembles other similar findings in the surgical literature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[11][12][13] A recent institutional study by Lipschitz and colleagues demonstrated that obesity was not a risk factor for most post-operative complications. 22 Similar to that study, we found increased BMI to be associated with post-operative cardiovascular complications, which is in-line with previous studies acknowledging obesity as a risk factor for MI. 23 Though our observed association between obesity and wound infections or severe obesity and DVT are not in-line with Lipschitz et al, 22 these finding resembles other similar findings in the surgical literature.…”
Section: Discussionsupporting
confidence: 92%
“…22 Similar to that study, we found increased BMI to be associated with post-operative cardiovascular complications, which is in-line with previous studies acknowledging obesity as a risk factor for MI. 23 Though our observed association between obesity and wound infections or severe obesity and DVT are not in-line with Lipschitz et al, 22 these finding resembles other similar findings in the surgical literature. [24][25][26] This manuscript further strengthens their conclusion by demonstrating similar rates of LOS, readmission, reoperation, pulmonary embolism, pneumonia, urinary tract infection, and septic shock rates, which were not evaluated by Lipschitz and colleagues.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, we observed that discharge to a care facility and LOS were positively associated with short-term adverse events. BMI did not influence morbidity following transcervical surgery, resembling the findings of Crippen et al 29 and Lipschitz et al 31 in head and neck free flap and vestibular schwannoma surgeries, respectively. Similar to the literature concerning a wide variety of surgical fields, 16,25,32,33 this study demonstrated that smoking, with an OR of 2.1 on multivariate analysis, was predictive of short-term adverse events.…”
Section: Discussionsupporting
confidence: 82%
“…BMI did, however, show a negative association with good postoperative FN outcomes, although not at latest follow-up. Previous literature on effects of BMI vary, with some studies showing no association of obesity with complications 58 and with others showing an association with an increased rate of complication, 57 a longer hospital stay, 59 and development of postoperative cerebrospinal fluid leaks. 60 To our knowledge, there has not been a study directly examining the association of BMI with FN outcomes following surgery for VS.…”
Section: Predictive Factors Of Fn Functional Outcomesmentioning
confidence: 99%